757 Cardio-TC role in patients selection for transcatheter edge to edge tricuspid repair. (8th December 2021) - Nobile, Edoardo; Cammalleri, Valeria; De Stefano, Domenico; Vitez, Luka; De Filippis, Aurelio; Paolucci, Luca; Carpenito, Myriam; Bono, Maria Caterina; Mega, Simona; Nusca, Annunziata; Grigioni, Francesco; Ussia, Gian Paolo
Abstract: Aims: Anatomic knowledge of the tricuspid valve (TV) is the first step in the management of patients with tricuspid regurgitation (TR) who are candidates for transcatheter tricuspid valve intervention (TTVI). Echocardiography is undoubtedly the first approach in assessing the aetiology and severity of TR and the size and function of the right chambers. Computed tomography (CT) provides a detailed morphological visualization of the cardiac structures owing to acquisition of 3D data with high spatial resolution. These findings may undoubtedly help in decision-making progress for novel transcatheter therapies. The purpose of the present study was to assess the geometrical changes of the TV complex using CT images, in patients suffering from functional TR and lead-induced TR. Methods: The study population consisted of 21 consecutive patients with symptomatic severe TR referred to Policlinico Universitario Campus Biomedico between November 2020 and October 2021. Patients were prospectively included in the study only if they presented severe TR, diagnosed by echocardiography and underwent cardiac CT study dedicated to the right-chambers. The reconstructions were transferred to an external workstation for off-line image analysis. The following measurements were reported: tricuspid annulus area, perimeter, septal–lateral and antero-posterior diameters. Commissures were identified as antero-septal (AS), postero-septal (PS) and anteroposterior (AP). Were measured the inferior vena cava ostium to tricuspid valve centroid distance, anatomic regurgitant orifice area (AROA) and its position respect to the centroid, and the right chambers. Results: All 21 patients underwent CT scan using Siemens SOMATOM Definition AS 128 Slice CT Machine. The measurements were calculated off-line using the 3mensio workstation. In our study population, the annulus resulted enlarged in the annulus area, perimeter, septal-lateral and anterior-posterior dimensions. Measurements did not differ significantly, except for the septal-lateral diameter that was smaller in systole (52.80 ± 7.28 mm vs. 47.83 ± 6.83 mm ( P =0.027). Also, distances between the commissures were similar except for the AP-AS distance that was shorter in systole (45.26 ± 3.48 mm vs. 42.13 ± 3.73, P =0.007). The AROA resulted to be central in 7 patients, the IVC ostium to TV centroid distance was 23±3 mm. Right chambers and IVC resulted very enlarged in all patients. Conclusions: CT provides a complete morphologic imaging of the heart structures, thanks to a high spatial resolution with excellent capacity to define the endocardial border and allows acquisition of three-dimensional data with high spatial resolution of the TV and provides valuable information about the geometric variations of the tricuspid complex in patients with TR. Image quality for analysis should be optimized with specific CT acquisition protocols that focus on the right ventricles.